Refórmese el numeral 1 del artículo 74 del código de la niñez y adolescencia, para garantizar los derechos de los niños, niñas y adolescentes - Quezada Ordoñez, Victor Hugo (2016)
The Ecuadorian Constitution guarantees children and adolescents protection and comprehensive protection, in order to achieve development and the full enjoyment of their constitutional rights. It is therefore necessary to consider them as legal subjects and not as objects of protection, thus allowing to know which are subject to the application of measures to ensure their development. The same that is based on the principle of "best interests of the child", which prevails even over those of others. The Bill of Rights in the Convention on the Rights of the Child, Ecuador is committed to make effective the enforcement of the rights enshrined in the international instrument, thus becoming a reference framework, and defend respect for human rights this group of people, not as objects of law, but as rights holders, as established in the art. 10 our supreme law. For all the aforementioned it is necessary to make a proposal for a legal amendment to paragraph 1 of Article 74 of the Code of Children and Adolescents, to implement policies and programs to provide assistance to children and adolescents and persons responsible for their care and protection, according to the principle of the best interests and the doctrine of comprehensive protection, to thereby prevent any form of violation of rights.